Adjuvant atezolizumab versus placebo for patients with renal cell carcinoma at increased risk of recurrence following resection (IMmotion010): a multicentre, randomised, double-blind, phase 3 trial. Issue 10358 (1st October 2022) - Pal, Sumanta Kumar; Uzzo, Robert; Karam, Jose Antonio; Master, Viraj A; Donskov, Frede; Suarez, Cristina; Albiges, Laurence; Rini, Brian; Tomita, Yoshihiko; Kann, Ariel Galapo; Procopio, Giuseppe; Massari, Francesco; et al.
Summary: Background: The standard of care for locoregional renal cell carcinoma is surgery, but many patients experience recurrence. The objective of the current study was to determine if adjuvant atezolizumab ( vs placebo) delayed recurrence in patients with an increased risk of recurrence after resection. Methods: IMmotion010 is a randomised, double-blind, multicentre, phase 3 trial conducted in 215 centres in 28 countries. Eligible patients were patients aged 18 years or older with renal cell carcinoma with a clear cell or sarcomatoid component and increased risk of recurrence. After nephrectomy with or without metastasectomy, patients were randomly assigned (1:1) to receive atezolizumab (1200 mg) or placebo (both intravenous) once every 3 weeks for 16 cycles or 1 year. Randomisation was done with an interactive voice-web response system. Stratification factors were disease stage (T2 or T3a vs T3b–c or T4 or N+ vs M1 no evidence of disease), geographical region (north America [excluding Mexico] vs rest of the world), and PD-L1 status on tumour-infiltrating immune cells (<1% vs ≥1% expression). The primary endpoint was investigator-assessed disease-free survival in the intention-to-treat population, defined as all patients who were randomised, regardless of whether study treatment was received. The safety-evaluable population included all patients randomly assigned to treatment who received any amount of study drug (ie, atezolizumab or placebo), regardless of whether a full or partial dose was received. This trial is registered with ClinicalTrials.gov, NCT03024996, and is closed to further accrual. Findings: Between Jan 3, 2017, and Feb 15, 2019, 778 patients were enrolled; 390 (50%) were assigned to the atezolizumab group and 388 (50%) to the placebo group. At data cutoff (May 3, 2022), the median follow-up duration was 44·7 months (IQR 39·1–51·0). Median investigator-assessed disease-free survival was 57·2 months (95% CI 44·6 to not evaluable) with atezolizumab and 49·5 months (47·4 to not evaluable) with placebo (hazard ratio 0·93, 95% CI 0·75–1·15, p=0·50). The most common grade 3–4 adverse events were hypertension (seven [2%] patients who received atezolizumab vs 15 [4%] patients who received placebo), hyperglycaemia (ten [3%] vs six [2%]), and diarrhoea (two [1%] vs seven [2%]). 69 (18%) patients who received atezolizumab and 46 (12%) patients who received placebo had a serious adverse event. There were no treatment-related deaths. Interpretation: Atezolizumab as adjuvant therapy after resection for patients with renal cell carcinoma with increased risk of recurrence showed no evidence of improved clinical outcomes versus placebo. These study results do not support adjuvant atezolizumab for treatment of renal cell carcinoma. Funding: F Hoffmann-La Roche and Genentech, a member of the Roche group.